Conversion due to vascular injury during video-assisted thoracic surgery lobectomy: A multicentre retrospective analysis from the Italian video-assisted thoracic surgery group registry. Issue 5 (May 2019) - ,; Bertolaccini, Luca; Davoli, Fabio; Pardolesi, Alessandro; Brandolini, Jury; Argnani, Desideria; Bertani, Alessandro; Droghetti, Andrea; Gonfiotti, Alessandro; Divisi, Duilio; Crisci, Roberto; Solli, Piergiorgio; et al.
Abstract: Objectives: Vascular injuries are among the most severe causes of unplanned conversion during VATS lobectomies. The study aimed to analyse the incidence of vascular injuries and their risk factors during VATS lobectomy. Methods: The Italian VATS lobectomy Registry was used to collect data from 66 Thoracic Surgery Units. From 2013 to October 2016 (out of more than 3, 700 patients enrolled) only information from Units with an enrollment >100 VATS lobectomies were retrospectively analysed. Logistic regression analysis was performed on selected variables of the univariate analysis. Results: Ten institutions contributed a total of 1, 679 patients. Vascular injuries leading to conversion occurred in 44 (2.6%) patients. Years of experiences were inversely related to the risk of vascular injuries. Univariate analysis showed age, gender, surgical activity, Charlson Index Score and number of resected lymph nodes like significantly associated variables. Multivariate analysis revealed that number of resected lymph nodes, VATS experience ratio (number of VATS lobectomies/total lobectomies performed in the same year at same centre), and surgical activity of the centre were significantly associated with the risk of conversion. Unplanned thoracotomy was correlated with postoperative morbidity. Conclusion: Vascular injuries in VATS lobectomies represented a rare complication which could directly affect the postoperative outcomes. The predictive factors for conversion were multifactorial and depended on characteristics of centres and surgeons' seniority. Minimally invasive VATS lobectomy approaches did not influence the risk of vascular damages.